2010
DOI: 10.1007/s00125-010-1823-8
|View full text |Cite
|
Sign up to set email alerts
|

The glucagon-producing alpha cell: an electrophysiologically exceptional cell

Abstract: Activation of potassium channels normally serves to reduce cellular activity but recent data indicate that the glucagon-secreting alpha cells are different in this respect and that inhibition of voltage-gated potassium channels results in a paradoxical inhibition of glucagon secretion. Here we discuss these findings and attempt to provide a model for the regulation of glucagon secretion that incorporates these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It has been observed that α-cells are electrically active [33] and contain electrically active Ca 2+ channels [34]. Several reports have indicated that entry of extracellular Ca 2+ is required for glucagon release, whereas others have reported that glucagon can be released in the absence of Ca 2+ [3537].…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that α-cells are electrically active [33] and contain electrically active Ca 2+ channels [34]. Several reports have indicated that entry of extracellular Ca 2+ is required for glucagon release, whereas others have reported that glucagon can be released in the absence of Ca 2+ [3537].…”
Section: Resultsmentioning
confidence: 99%
“…With inhibition of the K v current, there is no reactivation of the Na v channels and Ca v channels leading to a marked reduction of the action potential amplitude, thereby inhibiting glucagon release. As a consequence, glucagon secretion is decreased when K v channels are blocked 8,29,30 or dysfunctional as in LQT2 patients. Therefore, LQT2 patients have impaired counterregulatory defense against hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation of the Na + channels occurs during the interval between two successive action potentials and the inter-spike membrane potential, which in turn is influenced by the number of voltage-dependent K + channels activated during the action potential; the stronger the activation of K + channels, the more negative the inter-spike membrane potential and the greater the reactivation of Na + channels. This may explain the paradox that blocking voltage-gated K + channels in alpha cells is associated with inhibition of glucagon secretion and electrical activity rather than the stimulation seen in beta cells [49][50][51].…”
Section: Ion Channels and Islet Cell Electrical Activitymentioning
confidence: 99%